EFFECT OF ZEOLITES SPEREADING ON LITTERS TO BROILER PERFORMANCES REARED UNDER DIFFERENT FLOOR SPACES - Kardaya, Dede; Ulupi, Niken (Jurnal Zeolit Indonesia, 2006)
Effect of zeolites spreading on litters to broiler performances under different floor spaces had been performed in five weeks. As many as 324 chicks of a day-old Hubbard strain were fed rations contained 3,000 â 3,100 Kcal/Kg ME and 21% crude protein during starter period and fed the ration contained 20% crude protein with similar energy during finisher period. The chicks were randomly allocated to three different floor spaces (10, 12, and 14 heads/m2) and three different zeolites spread-litters (0.0, 2.5, and 5.0 kg zeolites/m2) under completely randomized design with factor 3 x 3 and 3 replications. Parameters concerned of present research including feed intake, live weight gain, and mortality rate were analyzed with analysis of variance (ANOVA) and least significant different (LSD). Results of the present research showed that there was no interaction effect between floor spaces and zeolites spread litters on all parameters concerned. Floor spaces affected both feed intake (P